STRATEGI EKSPANSI DAKWAH ISLAMIAH PADA MASA DINASTI UMAYYAH: STUDI KASUS PENAKLUKAN AFRIKA UTARA DAN SPANYOL - Nasution, Muhammad Afrezal; Zulaikha, Dira; Lubis, Azriel Ivan Akbar; Akmal, Fathurrahman; Akbar, Muhammad Habib; Sabrina, Raisyah Amalia; Windari, Sri (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
This research examines the Islamic dakwah expansion strategies implemented by the Umayyad Dynasty, focusing on the conquests of North Africa and Spain as case studies. The Umayyad Dynasty not only expanded political power but also spread Islamic teachings to various nations and cultures. Employing a descriptive historical method, this study analyzes how factors such as military strength, centralized administration, and cultural acculturation contributed to the success of dakwah expansion. The main findings reveal that the Umayyad dakwah expansion involved a complex interplay of conquest, cultural adaptation, and the construction of infrastructure that supported the spread of Islam. In conclusion, the Umayyad Dynasty's expansion strategies laid the foundation for a broader and more diverse development of Islamic civilization.